2021
DOI: 10.1002/tee.23320
|View full text |Cite
|
Sign up to set email alerts
|

Soft Errors in Logic LSI Due to Electric Field Noise Caused by Corona Discharge Air Ionizer

Abstract: Corona discharge air ionizers are widely used during quality control inspections to neutralize the static electricity on electronic devices because the electric field generated by static charge can lead to soft errors. However, an air ionizer may act as a source of noise, which can also lead to soft errors, because it creates a large number of ions that generate a high‐intensity electric field. The soft errors of a CMOS inverter in a large‐scale integration (LSI) were investigated in a minienvironment in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Taking Shandong Province as an example, there are a considerable number of ultra-high voltage transmission lines in Shandong that pass through areas with varying degrees of contamination, leading to complex distributions of audible noise. Studies by scholars [4][5] have shown that the surface condition of conductors has a significant impact on corona sparking and the resulting interference (acoustic noise, radio interference, etc. ); the presence of contaminants on the conductor surface reduces the onset voltage of corona sparking and increases audible noise.…”
Section: Introductionmentioning
confidence: 99%
“…Taking Shandong Province as an example, there are a considerable number of ultra-high voltage transmission lines in Shandong that pass through areas with varying degrees of contamination, leading to complex distributions of audible noise. Studies by scholars [4][5] have shown that the surface condition of conductors has a significant impact on corona sparking and the resulting interference (acoustic noise, radio interference, etc. ); the presence of contaminants on the conductor surface reduces the onset voltage of corona sparking and increases audible noise.…”
Section: Introductionmentioning
confidence: 99%
“…AC corona discharge air ionizers have been used to neutralize electrostatic charge and prevent the hazard. However, the corona ionizers themselves may be a cause of ESD damage and/or soft errors because the high voltage applied to the emitter and the space charge of the ions generated by the ionizers generate high intensity electric field [2]. Therefore, it is proposed to install an electric field shield between the ionizer and the worktable to prevent electrostatic hazard [3].…”
Section: Introductionmentioning
confidence: 99%